What Really Matters for Loneliness Among Left-Behind Children in Rural China: A Meta-Analytic Review - Chai, Xiaoyun; Du, Hongfei; Li, Xiaoyan; Su, Shaobing; Lin, Danhua (Frontiers in Psychology, 2019)
In rural China, left-behind children are likely to suffer chronic loneliness. Research has identified a variety of factors that may be associated with loneliness among these children. A meta-analysis is needed to address the empirical inconsistencies and examine the strength of relations between different factors and loneliness. The current meta-analysis included 51 studies on predictors (e.g., self-esteem) of loneliness published from 2008 to 2017. Results showed that one individual factor (social anxiety) is a key risk factor for loneliness, whereas eight individual (older age, self-esteem, resilience, extroversion) and contextual factors (family functioning, parent‒child relationship, peer relationship, social support) serve as protective factors in predicting loneliness. In addition, boys were more likely to feel lonely than girls. Findings and implications of this study were discussed.